Male fertility: a review of the publications from October - December 2020 - D. S. Rogozin (Вестник урологии)
The article provides an overview of the most significant publications on the topic of male infertility. The main selection criteria were considered the practical significance of the article, as well as the impact factor of the journal in which it was published, according to the SCImago Journal Rank (SJR). As a result, a list of 10 papers was formed that published from October - December 2020. The review included articles on the following issues: sperm DNA fragmentation and oxidative-reductive balance in the male reproductive system, advanced paternal age, hormonal stimulation in patients with nonobstructive azoospermia, the relationship of cancer with infertility, as well as embryological methods to increase the effectiveness of assisted reproductive technologies procedures.